Faktor yang Mempengaruhi Minat Beli Terhadap Waralaba Cepat Saji Asing - Angelina, Angelina; Zai, Immanuel (Universitas Islam Kadiri, 2023)
The purpose of this study is to find out which factors influence purchase interest as mediated by customer satisfaction in international fast food restaurants in Batam city. This study is comprehensive with quantitative methods, the sampling technique of this study is non-random (purposive sampling). This study involved 256 respondents from Batam City who visited international fast food restaurants. These research data were processed and analyzed using the SMART-PLS structural equation modeling program. Research results show that brand image and green marketing have a significant positive effect on purchase interest, while product quality variables do not have a positive effect on purchase interest. Brand image and product quality have a significant positive effect on customer satisfaction, while green marketing does not have a significant positive effect and customer satisfaction has a significant positive effect on purchase intentions. Brand image and product quality significantly affect purchase intentions, which are mediated by customer satisfaction, unlike green marketing, where the results are positive and insignificant.